Integrating Bricolage into Project Management : Evidence from a Software Startup Leveraging Limited Resources - Rana, Bishal (My University, 2026)
Software startups are frequently categorized as organizations operating under uncertainty and resource constraints, making their operational context distinct from mature organizations. As a result, prior literature has provided limited understanding of project management practices and framed such practices as informalities and deviations from standard methodologies such as agile or lean practices. The current study aims to shift this perspective by introducing the foundations of “Bricolage” into project management, which has been underexplored in prior studies. Bricolage is a concept which has been widely used in contexts where resources are scarce and enables creative, unconventional and strategic use of existing resources. However, the application and use of bricolage in project management is in its embryonic stages. Therefore, the study employs a single organization case study as the primary source of data collection which includes semi-structured interviews with the co-founders and active participant observation by the researcher. Similarly, the data is triangulated using an informal subjective survey which has been minimally used to validate the primary data. The data is collected based on an interpretivist and inductive approach where the collection is based on the observed practices and interactions as the project progresses. Consequently, the data has been coded thematically and key themes for the study has been generated which are based on empirical data collection. The key themes generated by the study include pragmatic adoption of tools, maximization of resources, informal execution, usage of generative and agentic AI tools and normalization of informalities. Finally, the data has been analyzed through the theoretical frameworks of bricolage, agile and lean enabling the findings to be grounded to the theoretical instances. The analysis reports that the foundations of bricolage could better describe the project management approaches in startups and could possibly accelerate agility in certain conditions. Finally, the study contributes to the body of project management by providing a novel direction towards the exploration of bricolage practices in agile approaches and practically, it encourages practitioners to view constraints as catalyst for creative and strategic resourcefulness. However, the resulting effect of bricolage in the long run requires a longitudinal study which has been realized, and future researchers are directed to explore further to uncover the aftermath of bricolage in diverse contextual settings.
Keywords: startup companies; project management; entrepreneurship; software development; project leadership; projects; agile methods; lean thinking; research methods; Strategic Project Management; Master’s Programme in Industrial Engineering and Management